Pengaruh Elemen Elemen Brand Equity terhadap Keputusan Pembelian Konsumen Produk Eiger - Mochammad Mahmudi Rosid; Widyastuti Widyastuti (BISMA (Bisnis dan Manajemen), 2018)
Increased activity of wild adventure and sports create demand for the product as a complement to the more adventurous, this is used by the equipment manufacturer adventure to compete for a place in the hearts of consumers. PT Eigerindo Multi Industrial Products, which is a manufacturer of products for the adventure out a few brands that is Nordwand, Eiger Women Series, Bodypack, and EIGER own. The strategy used is the application of the elements of brand equity in the minds of consumers, so the presence of elements of brand equity can affect purchasing decisions. This study aims to discuss and analyze the influence of the elements of brand equity is brand awareness, perceived quality, brand association and brand loyalty simultaneously and partial response to consumer purchasing decisions EIGER products, as well as to determine the variables most dominant influence. Where brand awareness, perceived quality, brand association and brand loyalty becomes the independent variable (X) and purchasing decisions become dependent variable (Y). The population in this study is consumers who have been involved in the purchase of products EIGER, namely Surabaya community EIGER product users. Sampling methods were studied non-probability sampling using accidental sampling technique with 110 respondents. Analysis technique used is multiple linear regression analysis processed through SPSS version 17.0 Hypothesis testing conducted using the F test and t test. The results of this study  which means that there are simultaneous and partial influence on purchasing decisions Eiger products is equal 52,6%, while the remaining balance of 47.4% influenced by other variables outside of variables in this study. While one of independent variable is not significant influence is perceived quality. The most influential variable the dominant is brand loyalty.